Use of Social Media in Branding Management of Educational Institutions - Audina, Mia; Salindry, Agesta Eka; Wigati, Indah; Yuniar, Yuniar (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research aims to determine the influence of social media in supporting the implementation of management of educational institutions at Integrated Islamic Schools for Junior High Levels A, B and C in the city of Palembang. This research is a type of descriptive qualitative research; the data collection method used is interview techniques, observation and literacy studies. The data analysis stages in this research are data collection, data reduction, data presentation and concluding (verification). The results of this research show that the use of social media in schools A, B and C has a significant influence where the use of social media in supporting the implementation of school management in school branding, learning media and communication facilities between the school, parents and the general public can be implemented well.